FAMILY, SCHOOL AND COMMUNITY COOPERATION IN TEACHING ADOLESCENT STUDENTS SELF-AWARENESS AND SELF-MANAGEMENT - Q.B.Djurayev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, family, school and community cooperation in teaching adolescent students to self-awareness and self-management, as well as pedagogical research conducted under specific conditions, aimed at improving the educational environment of a growing person. only, it acquires scientific and practical importance. Research results serve to create an educational environment for social practice. From a social point of view, thoughts and opinions are given about helping to expand the educational opportunities of the microenvironment during the regular development of each young person growing up from a social point of view, and from a pedagogical point of view, creating specific conditions for the holistic educational process of the school and extra-school microenvironment (family, neighborhood).